Computational Intelligence in Medical Informatics - Muppalaneni, Naresh Babu; Gunjan, Vinit Kumar (SpringerBriefs in Forensic and Medical Bioinformatics, 2015)
This Brief highlights Informatics and related techniques to Computer Science Professionals, Engineers, Medical Doctors, Bioinformatics researchers and other interdisciplinary researchers. Chapters include the Bioinformatics of Diabetes and several computational algorithms and statistical analysis approach to effectively study the disorders and possible causes along with medical applications.